Genomic insights of mcr-1 harboring Escherichia coli by geographical region and a One-Health perspective - Calero-Cáceres, William; Rodríguez, Kerly; Medina, Anabell; Medina, Jennifer; Ortuño-Gutiérrez, Nimer; Sunyoto, Temmy; Dias, Cícero Armídio Gomes; Bastidas-Caldes, Carlos; Ramírez, Maria Soledad; Harries, Anthony David (Frontiers in Microbiology, 2023)
The importance of the One Health concept in attempting to deal the increasing levels of multidrug-resistant bacteria in both human and animal health is a challenge for the scientific community, policymakers, and the industry. The discovery of the plasmid-borne mobile colistin resistance (mcr) in 2015, poses a significant threat because of the ability of these plasmids to move between different bacterial species through horizontal gene transfer. In light of these findings, the World Health Organization (WHO) recommends that countries implement surveillance strategies to detect the presence of plasmid-mediated colistin-resistant microorganisms and take suitable measures to control and prevent their dissemination. Seven years later, ten different variants of the mcr gene (mcr-1 to mcr-10) have been detected worldwide in bacteria isolated from humans, animals, foods, the environment, and farms. However, the possible transmission mechanisms of the mcr gene among isolates from different geographical origins and sources are largely unknown. This article presents an analysis of whole-genome sequences of Escherichia coli that harbor mcr-1 gene from different origins (human, animal, food or environment) and geographical location, to identify specific patterns related to virulence genes, plasmid content and antibiotic resistance genes, as well as their phylogeny and their distribution with their origin. In general, E. coli isolates that harbor mcr-1 showed a wide plethora of ARGs. About the plasmid content, the highest concentration of plasmids was found in animal samples. In turn, Asia was the continent that led with the largest diversity and ocurrence of these plasmids. About virulence genes, terC, gad and traT represents the most frequent virulence genes detected. These findings highlight the relevance of analyzing the environmental settings as an integrative part of the surveillance programs to understand the origins and dissemination of AMR.